Loki (2023) ebook The liar. - Watters, Dan (Loki (2023), 2024)
Collects Loki (2023) #1-4. The fate of the Marvel Universe lies in the hands of…Loki?! He may be the ''benevolent'' God of Stories now, but his past as the God of Lies returns to haunt him when something ancient and powerful that he once built ends up scattered across the Ten Realms! Now, setting sail on a ship made of fingernails, the Trickster must track down its fragments to stave off Ragnarok! His epic journey begins in the ruins of Nidavellir, where the relic has been crafted into a devastatingly powerful weapon! Then, on a distant planet, will Emperor Hulkling and Wiccan put aside old grudges against their former Young Avengers teammate to aid Loki's quest? And what happens when the third shard ends up in the hands of Earth's deadliest assassin? There's a target on Loki's back, and Bullseye never misses!